ANALYSIS OF CARBON TRADING REGULATIONS AND THEIR CONTRIBUTION TO ACHIEVING INDONESIA’S NATIONAL EMISSION REDUCTION TARGETS - Riska Sari; Muhammad Fariz; Daniel Allan Rosen (EQUALEGUM International Law Journal, 2026)
Background. Climate change has become one of the most pressing global challenges, prompting countries to adopt various policy instruments to reduce greenhouse gas (GHG) emissions. Indonesia, as a party to the United Nations Framework Convention on Climate Change and the Paris Agreement, has committed to reducing emissions through its Nationally Determined Contribution (NDC). One of the key regulatory innovations introduced by the Indonesian government is carbon trading under Presidential Regulation No. 98 of 2021 concerning the Economic Value of Carbon. This study analyzes the effectiveness of Indonesia's carbon trading regulatory framework in supporting national emission reduction targets. Research Methods. Employing a normative legal research design, this study examines Indonesia's legal framework for carbon trading. It analyzes statutory regulations, international legal instruments, and comparative practices to assess the effectiveness of existing norms in aiding Indonesia's greenhouse gas emission reduction goals. The analysis includes constitutional provisions, national and sector-specific legislation, and relevant international agreements. A comparative approach highlights best practices and identifies regulatory gaps, suggesting potential reforms to enhance Indonesia's carbon trading and support sustainable development objectives. Findings. The findings indicate that Indonesia has established a comprehensive legal foundation for carbon trading; however, challenges remain regarding institutional coordination, market transparency, carbon credit verification, and legal certainty. While carbon trading has significant potential to contribute to national emission reduction targets, its effectiveness depends on regulatory coherence, robust monitoring systems, and alignment with international carbon market standards. Conclusion. Strengthening governance mechanisms, improving transparency, and integrating carbon trading into broader climate policy frameworks.